Early-stage macular telangiectasia type 2 vascular abnormalities are associated with interdigitation zone disruption - Janice X. Ong (Public Library of Science (PLoS), 2021)
Purpose To investigate the relationship between disruption in different photoreceptor layers and deep capillary plexus (DCP) telangiectasias in eyes with macular telangiectasia type 2 (MacTel). Methods 35 eyes (21 patients) with MacTel imaged with optical coherence tomography angiography (OCTA) were included. Circumscribed areas of DCP telangiectasia were traced from OCTA slabs and the corresponding spectral-domain OCT (SD-OCT) slabs were used to visualize the photoreceptor layer interdigitation zone (IZ) and ellipsoid zone (EZ). IZ attenuation, IZ loss, and EZ loss were graded by reviewing en face SD-OCT slabs for hypo-reflective areas and confirming their status on cross-sectional views. Total area of photoreceptor disruption and overlap with DCP telangiectasia were evaluated with respect to OCT-based MacTel stage. Longitudinal changes were evaluated in a subset of patients with follow-up imaging. Results Overlap of DCP telangiectasia with IZ attenuation significantly decreased with MacTel severity, while overlap with IZ and EZ loss significantly increased. Overlap with IZ loss peaked in moderate MacTel (Stages 3–5). Longitudinal imaging showed that new EZ loss at 6 months was largely predicted by baseline IZ loss. Conclusions Worsening MacTel severity is characterized by greater overlap between DCP telangiectasia and zones of increasing severity of photoreceptor disruption, with EZ loss enlarging over time within areas of preexisting IZ disruption. We suggest that IZ disruption may indicate early photoreceptor dysfunction that eventually progresses to EZ loss, with IZ loss being a more reliable metric than IZ attenuation. Additional studies will be necessary to further explore long-term photoreceptor changes and evaluate their relationship with visual function in MacTel.